The Black worker from the founding of the CIO to the AFL-CIO merger, 1936-1955 - Foner, Philip Sheldon, 1910-1994; Lewis, Ronald L., 1940-; Ervin, Keona K. (Black worker, 2019)
"Volume seven is among the richest of the collection because of the high rates of labor union mobilization and worker self-organization that went on during the 1930s and 1940s. The Congress of Industrial Organizations and its mass organizing efforts that included Black workers receives considerable attention. The organizing efforts of the Steel Workers Organizing Committee, which we learn supported federal anti-lynching legislation, the National Negro Congress, and the Southern Tenant Farmers' Union are documented through sources drawn from Black newspapers, Communist publications such as The Daily Worker, library archives, the records of civil rights organizations, and the papers of Franklin D. Roosevelt."